The effect of compression and combined compression-tactile stimulation on lower limb somatosensory acuity - Marchant, Ashleigh; Wallwork, Sarah B.; Ball, Nick; Witchalls, Jeremy; Waddington, Gordon (Frontiers in Sports and Active Living, 2023)
Background Lower limb somatosensation and proprioception are important for maintaining balance. Research has shown that compression garments or exposure to textured surfaces, can enhance somatosensation however, little is known about the effect of combined compression and texture on somatosensory acuity in the lower limb. This study aimed to assess the effects of combined compression socks with a plantar textured sole, on lower limb somatosensory acuity. Methods Thirty participants completed a somatosensory acuity task (active movement extent discrimination apparatus; AMEDA) under three conditions: barefoot (control condition), standard knee-high compression sock (compression sock), and knee-high compression sock with internal rubber nodules situated on the sole (textured-compression sock). Somatosensory acuity was assessed between the different sock conditions for the (i) entire group, (ii) high performers, and (iii) low performers. It was hypothesized that low performers would see gains wearing either sock, but the greatest improvement would be in the textured-compression sock condition. Results AMEDA scores were not significantly different between conditions when the entire group was analyzed (p = 0.078). The low performers showed an improvement in somatosensory acuity when wearing the compression sock (p = 0.037) and the textured compression sock (p = 0.024), when compared to barefoot, but there was no difference between the two sock conditions (p > 0.05). The high performers did not show any improvement (p > 0.05 for all). Conclusion These findings demonstrate that additional sensory feedback may be beneficial to individuals with lower baseline somatosensory acuity but is unlikely to provide benefit for those with higher somatosensory acuity.